PENGARUH METODE EKSPERIMEN TERHADAP KETERAMPILAN PROSES SAINS ANAK USIA 5-6 TAHUN DI TK SALSABILA KECAMATAN RUMBAI PESISIR PEKANBARU - Marpa Pagaben, Sri Putri; solfiah, Yeni; ', Zulkifli (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Science process skills that have not been trained to be a problem inscience learning science process skills class children still far from expectations. This isbecause children are less given the opportunity to be directly involved in scienceexperiments. Learning methods that can involve children actively in observing theprocess and the results of the experiment is the experimental method. This is what liesbehind the researcher to conduct research with the aim to see the effect of theexperimental method to the science process skills of children in kindergarten SalsabilaRumbai Coastal District of Pekanbaru. The number of samples in this study were 15children. This study was an experimental study using one group design with pre-testand post-test through observation sheet. Results of the experiment showed scienceprocess skills of children in kindergarten Salsabila increased by 58.87%. From theresults of this study can be interpreted that the experimental method effectively used toimprove the science process skills of children aged 5-6 years in kindergartenSALSABILA Rumbai Coastal District of Pekanbaru.Keyword: Methods, Experiments and Science Process Skills